2014
DOI: 10.1111/ggi.12261
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic dysfunction is associated with cerebral white matter lesions (leukoaraiosis) in elderly patients without ischemic heart disease and stroke

Abstract: Aim: Cerebral white matter lesions (WML) are known to increase with age, as is left ventricular (LV) diastolic dysfunction with normal contraction. Although aging is a common risk factor, the link between these diseases is not fully understood. The aim was to clarify this relationship, using the ratio between early diastolic mitral inflow and early diastolic mitral annular tissue velocity (E/E'). E/E' measured by tissue Doppler echocardiography offers an indicator of the severity of LV diastolic dysfunction, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Some studies have reported the existence of correlations between cardiac dysfunction and brain abnormalities, between LV diastolic function and the severity of WMH, between the left ventricular ejection fraction and the severity of WMH, between the left ventricular ejection fraction and cognitive function, between systolic blood pressure and the severity of the WMH, and between diastolic blood pressure (or pulse pressure) and the severity of WMH . These present and previous data show the importance of increased pulse pressure as a risk factor for the presence of severe WMH.…”
Section: Discussionsupporting
confidence: 78%
“…Some studies have reported the existence of correlations between cardiac dysfunction and brain abnormalities, between LV diastolic function and the severity of WMH, between the left ventricular ejection fraction and the severity of WMH, between the left ventricular ejection fraction and cognitive function, between systolic blood pressure and the severity of the WMH, and between diastolic blood pressure (or pulse pressure) and the severity of WMH . These present and previous data show the importance of increased pulse pressure as a risk factor for the presence of severe WMH.…”
Section: Discussionsupporting
confidence: 78%
“…Populations with hypertension, diabetes, metabolic syndrome, chronic kidney disease, high serum total homocysteine levels, a history of smoking and vitamin D deficiency have been reported as high‐risk groups for WMH developing and becoming severe . Furthermore, our group has clarified that left ventricular diastolic dysfunction is associated with WMH in elderly patients without ischemic heart disease and stroke . Of the aforementioned risk factors, hypertension is considered the greatest risk factor for the progression of WMH.…”
Section: Introductionmentioning
confidence: 95%
“…3 We previously reported that the severity of left ventricular (LV) diastolic dysfunction is associated with the volume of cerebral WML. 4 However, the analysis could not be carried out by removing the effect of the common or specific risk factors that are known to be involved in the progression of LV diastolic dysfunction and/or cerebral WML, such as age, hypertension, diabetes mellitus, hyperlipidemia, smoking, obesity and so on. Consequently, whether LV diastolic dysfunction is directly associated with cerebral WML remained unclear.…”
Section: Left Ventricular Diastolic Dysfunction Is Directly Associatementioning
confidence: 99%